Comparative Risk of Renal Adverse Events in Patients Receiving Immune Checkpoint Inhibitors: A Bayesian Network Meta-Analysis - Liu, Kang; Qin, Zhongke; Xu, Xueqiang; Li, Ting; Ge, Yifei; Mao, Huijuan; Xing, Changying (Frontiers in Oncology, 2021)
Background Immune checkpoint inhibitors (ICIs) have brought a paradigm shift to cancer treatment. However, little is known about the risk of renal adverse events (RAEs) of ICIs-based regimens, especially ICIs combination therapy. Methods We carried out a network meta-analysis of randomized clinical trials (RCTs) to compare the risk of RAEs between ICIs-based regimens and traditional cancer therapy, including chemotherapy and targeted therapy. Subgroup analysis was conducted based on tumor types. Results 95 RCTs eligible involving 40,552 participants were included. The overall incidence of RAEs, grade 3-5 RAEs, acute kidney injury (AKI) and grade 3-5 AKI was 4.3%, 1.2%, 1.3% and 0.8%, respectively. Both ICIs-based treatment regimens and traditional cancer therapy showed significantly higher risk of RAEs and AKI compared with placebo. Among ICIs monotherapy, anti-PD-1 (RR, 0.51; 95% CI, 0.29-0.91) was significantly safer than anti-CTLA-4 in terms of RAEs. Anti-CTLA-4 showed significantly higher toxicity than anti-PD-1 (RR, 0.33; 95％CI, 0.14-0.77), anti-PD-L1 (RR，0.38；95％CI，0.16-0.91), and anti-PD-1 plus anti-CTLA-4 (RR，0.32；95％CI，0.12-0.87) in terms of grade 3-5 RAEs. The difference was not significant between ICIs monotherapy and traditional cancer therapy except that targeted therapy seemed to be the least toxic therapy in terms of the incidence of AKI. Dual ICIs regimens were not associated with higher risk of RAEs or AKI except that anti-CTLA-4 plus anti-PD-1 (RR，1.61；95％CI，1.02-2.56) was associated with higher risk of RAEs compared with anti-PD-1. ICIs plus chemotherapy showed increased risk of both RAEs and AKI compared with ICIs monotherapy, chemotherapy and targeted therapy. The overall results remained robust in meta-regression and sensitivity analyses. Conclusions Among ICIs monotherapy, anti-CTLA-4 appeared to be associated with increased toxicity, especially in terms of grade 3-5 RAEs. Dual ICIs regimens were not associated with higher risk of RAEs or AKI except that compared with anti-PD-1, anti-CTLA-4 plus anti-PD-1 was associated with higher risk of RAEs. ICIs plus chemotherapy seemed to be the most toxic treatment regimen in terms of RAEs, AKI and grade 3-5 AKI.